"IT'S LIKE A SHOULDER TO LEAN ON": SOCIAL SUPPORT PROVIDED BY AN INNER‐CITY WORKFORCE DEVELOPMENT PROGRAM. Issue 3 (31st January 2017) - Powell, Terrinieka W.; Jo, Meghan; Martin, Christopher; Philip, Winston; Astone, Nan M.
Abstract : The goal of this study was to examine the types of social support provided by STRIVE, an inner‐city‐based workforce development program. Life history interviews were conducted with 20 African American graduates (aged 18–24 years) of the workforce development program. Nearly half of the sample was male (45%). Over half of the sample was employed at the time of the interview (65%). Participants described receiving extensive informational and emotional support from the workforce development program. After participating in the workforce development program, respondents described themselves as being less stressed and more self‐confident. Participants described using the skills gained and support offered to gain employment, enroll in educational programs, and interact more effectively with others. Thus, workforce development programs may be a viable option to address employment needs and provide meaningful support to vulnerable young people during their transition into adulthood.